Fulfillment of customary obligations as an alternative punishment (Study in Wet Sesait Indigenous Community) - Atika Zahra Nirmala; Aryadi Almau Dudy; Suheflihusnaini Ashady; Ayu Riska Amalia (Institute Of computer Science (IOCS), 2024)
Indonesia recognizes several legal systems that apply in society, one of which is customary law. The purpose of this research is to find out the mechanism for fulfilling customary obligations as an alternative to punishment in the Wet Sesait indigenous community and to find out the position of fulfilling these customary obligations. This research is empirical legal research. The results showed that the fulfillment of customary obligations is carried out if there are Wet Sesait indigenous people who violate the rules that exist in the community where the settlement mechanism is through tau loka empat, while the position of fulfilling customary obligations as an alternative to punishment is more important than state law, where for all Wet Sesait people who commit violations even though these violations are also regulated in state law, namely criminal law, but the Wet Sesait community chooses to resolve through custom and sanctions will be carried out by tau lokak empat. So here is reflected the form of punishment in the Wet Sesait customary law community in the form of fulfilling customary obligations as an alternative to punishment carried out by the state.